2013
DOI: 10.1186/2193-1801-2-159
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of ethanol production from bagasse pith hydrolysate by a thermotolerant yeast Kluyveromyces sp. IIPE453 using response surface methodology

Abstract: Ethanol production from sugarcane bagasse pith hydrolysate by thermotolerant yeast Kluyveromyces sp. IIPE453 was analyzed using response surface methodology. Variables such as Substrate Concentration, pH, fermentation time and Na2HPO4 concentration were found to influence ethanol production significantly. In a batch fermentation, optimization of key process variables resulted in maximum ethanol concentration of 17.44 g/L which was 88% of the theoretical with specific productivity of 0.36 g/L/h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 23 publications
1
17
1
3
Order By: Relevance
“…In addition to the yeast S. cerevisiae , some of the thermotolerant yeasts were also previously used for the fermentation of biomass hydrolysates. Dasgupta et al . showed that the fermentation of the enzymatic hydrolysate of bagasse pith at 45 °C with the yeast strain Kluyveromyces sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the yeast S. cerevisiae , some of the thermotolerant yeasts were also previously used for the fermentation of biomass hydrolysates. Dasgupta et al . showed that the fermentation of the enzymatic hydrolysate of bagasse pith at 45 °C with the yeast strain Kluyveromyces sp.…”
Section: Resultsmentioning
confidence: 99%
“…It wass hown that the ethanol production reached 52.29 % of the maximal theoretical yield but was also accompanied by the formation of high levels of acidic compounds. In addition to the yeast S. cerevisiae,s ome of the thermotolerant yeasts were also previously used for the fermentation of biomass hydrolysates.D asgupta et al [73] showed that the fermentation of the enzymatic hydrolysateo fb agasse pith at 45 8Cw ith the yeast strain Kluyveromyces sp. IIPE45 resulted in an ethanol production of 0.36 gL À1 h À1 and 88 %o ft he theoretical yield on am ixture of hexoses, which is comparable with the data obtainedf or K. marxianus C1 in our study.…”
Section: Cultivation Of Thermotolerant Yeasts On the Extracted And Nementioning
confidence: 99%
“…A second order polynomial model, similar to that of Dasgupta et al (2013) Finally, the experiment was repeated in triplicate using the variables that gave the optimum bioethanol yield and the average of the results was compared to the optimum value. The validity of the model was adjudged to be good since the result is comparable to the optimum bioethanol yield to an extent.…”
Section: Design Of Experiment:-mentioning
confidence: 99%
“…22,23 However, on average, bagasse contains 35% pith, and with 60% depithing efficiency, about 20% pith is separated during depithing operation either at sugar mill site or at paper mill premises. 24 As the waste sieved out from bagasse paper and artificial fiber, bagasse pith also contains an amount of hemicellulose and cellulose. With a serious waste disposal problem, huge amount of bagasse pith has not been utilized, mainly used for combustion or the production of feed yeast.…”
Section: Introductionmentioning
confidence: 99%